Rohdea extrorsandra (Asparagaceae), a new species from north-eastern India - Odyuo, N.; Roy, Dilip Kr.; Averyanov, Leonid V. (Phytotaxa, 2017)
The genus Rohdea Roth (1821: 196) belonging to the family Asparagaceae (APG 2009) comprises 14 species and is distributed in South East Asia (Tanaka 2003, Averyanov et al. 2014, Govaerts 2016). In India, the genus includes 4 species namely R. delavayi (Franchet 1896: 40) Tanaka (2003: 331), R. eucomoides (Baker 1875: 581) Tanaka (2003: 332), R. nepalensis (Rafinesque 1838: 15) Tanaka (2010: 23) and R. wattii (Clarke 1889: 78) Yamashita & Tamura (2004: 369) (Hooker 1894, Liang & Tamura 2000).